The Effect of Microsilica on Expanding Cement for Micro-Annulus Problem in Gas Migration - Hamid, Muhammad Chairafy; Wardana, Raka Sudira; Pattinasarany, Adrian; Lian, Dan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Gas migration through cement slurry and micro-annuli remains a major well integrity. Improper cementation can lead to micro-annulus formation, enabling gas leakage and increasing blowout risk as downhole pressure decreases. Microsilica has been widely used as an anti-gas migration additive due to its ability to reduce permeability and improve cement stability; however, its effect on expanding cement systems has not been fully evaluated. This study investigates the influence of microsilica on the physical and mechanical properties of expanding cement slurry and its interaction with conventional expanding additives. Three slurry formulations—base slurry with microsilica, base slurry with expanding additive, and a combined microsilica–expanding additive system—were prepared and tested following API RP 10B procedures, including density, rheology, fluid loss, free water, thickening time, compressive strength, and expansion ring testing. Results show that microsilica provides beneficial effects by reducing fluid loss, eliminating free water, increasing compressive strength, and enhancing post-set expansion performance when combined with expanding additives. However, microsilica also increases slurry viscosity and shortens thickening time, potentially affecting pumpability and placement. Expansion ring tests indicate that the combined microsilica–expanding additive slurry exhibits the highest expansion (0.446% at 96 hours), whereas cement with microsilica alone shows initial shrinkage before gradual expansion. Overall, microsilica acts as a complementary additive that improves the performance of expanding cement but requires careful optimization to avoid negative impacts on rheology and setting behavior. The findings highlight the importance of additive balancing in designing cement systems for gas-migration-resistant well completions.